2008
DOI: 10.1186/cc7033
|View full text |Cite
|
Sign up to set email alerts
|

The adenosine deaminase inhibitor erythro-9-[2-hydroxyl-3-nonyl]-adenine decreases intestinal permeability and protects against experimental sepsis: a prospective, randomised laboratory investigation

Abstract: Introduction The treatment of septic conditions in critically ill patients is still one of medicine's major challenges. Cyclic nucleotides, adenosine and its receptors play a pivotal role in the regulation of inflammatory responses and in limiting inflammatory tissue destruction. The aim of this study was to verify the hypothesis that adenosine deaminase-1 and cyclic guanosine monophosphate-stimulated phosphodiesterase inhibition by erythro-9-[2-hydroxyl-3-nonyl]-adenine could be beneficial in experimental end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…The authors observed that endotoxemic rats, besides an increment of intestinal permeability, absorption capacity and mucosal damage, also showed an increase in the intestinal production of purines, hypoxanthine and uric acid. Under these conditions, the administration of EHNA improved bowel mucosal morphology, and was associated with an improvement of mucosal permeability and absorption capacity, thus corroborating the notion that adenosine deaminase is involved in the alterations of intestinal mucosa during endotoxemia, and that the inhibition of this enzyme could represent a novel therapeutic approach to manage the systemic inflammatory response associated with septic conditions [177].…”
Section: Adenosine Deaminase Inhibitorssupporting
confidence: 69%
See 1 more Smart Citation
“…The authors observed that endotoxemic rats, besides an increment of intestinal permeability, absorption capacity and mucosal damage, also showed an increase in the intestinal production of purines, hypoxanthine and uric acid. Under these conditions, the administration of EHNA improved bowel mucosal morphology, and was associated with an improvement of mucosal permeability and absorption capacity, thus corroborating the notion that adenosine deaminase is involved in the alterations of intestinal mucosa during endotoxemia, and that the inhibition of this enzyme could represent a novel therapeutic approach to manage the systemic inflammatory response associated with septic conditions [177].…”
Section: Adenosine Deaminase Inhibitorssupporting
confidence: 69%
“…Notably, the favorable effect of pentostatin on leukocyte-endothelial interactions was related to changes in adhesion molecule expression on inflammatory and endothelial cells [176]. A crucial role for adenosine deaminase in the maintenance of intestinal barrier integrity during sepsis was recently reported [177]. The authors observed that endotoxemic rats, besides an increment of intestinal permeability, absorption capacity and mucosal damage, also showed an increase in the intestinal production of purines, hypoxanthine and uric acid.…”
Section: Adenosine Deaminase Inhibitorsmentioning
confidence: 94%
“…ADA inhibitors can also have beneficial effects in hypertension and on myocardial ischemia as protective agents . The pharmacological inhibition of ADA is regarded as a therapeutic approach to counteract inflammation in several pathological conditions and may be potentially useful for the therapeutic management of intestinal inflammatory disorders . Recently, it has been suggested that inhibitors of ADA activity could contribute to the treatment of perinatal hypoxia–ischemia brain injury …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a close correlation has been found between the severity of inflammation and a local increase in both expression and activity of adenosine deaminase, the enzyme responsible for conversion of endogenous adenosine into inosine, which leads to a decreased availability of biologically active adenosine (Conlon and Law, 2004;Desrosiers et al, 2007). Based on this knowledge, the pharmacological inhibition of adenosine deaminase is regarded as a novel therapeutic approach to counteract inflammation in several pathological conditions (Adanin et al, 2002;Law et al, 2003;Kayhan et al, 2008). In line with this concept, we previously provided evidence on the protective effects exerted by drugs acting as adenosine deaminase inhibitors against the onset of experimental colitis.…”
Section: Introductionmentioning
confidence: 99%